Infestação de sitophilus zeamais na qualidade físico-química e microbiológica de grãos de trigo armazenados - Pintro, Tania Claudia (2015)
The objective of this study was to evaluate the effect of insect infestation Sitophilus zeamais on the physicochemical and microbiological quality in wheat grains, during storage in times of 0, 45, 90 and 135 days, in three temperatures: 20, 25 and 30 ºC. For the conduct of the experiment, wheat grain samples were collected (Triticum aestivum L.) of the cultivar BRS Tanager, produced in Western Paraná, from the harvest of 2013. For storage, the grains had water contents below 13%, being stored about 400 g in sealed glass containers with fabric type voil in order to facilitate gas exchange, totaling 72 containers stored in incubator BOD the temperature of 20, 25 and 30 ° C for 135 days. Of the total of containers, 36 were infested with 20 adults of Sitophilus zeamais and the other 36 were kept without infestation. Every 45 days, were samples for subsequent chemical-physical analysis (moisture, ash, and total protein population variation of insects), microbiological (filamentous fungi count and identification of fungi producing of deoxynivalenol) and quantifying of deoxynivalenol for the three temperatures at baseline and 135 days with and without infestation. The samples were evaluated by the use of analysis of variance (ANOVA) and for test of comparison of means the Tukey test was applied, with 5% level of significance. It was observed that, with increased storage time, increased population of insects, mainly at temperatures of 20 and 25° C, reducing the value of the weight of the hectolitre at both temperatures. In general, the water content was reduced with increasing temperature and time of the storage. The contents of protein, in the treatments with and without infestation, increased with storage time. In general, the ash content increased with time of storage in grain, with and without infestation in the three temperatures evaluated. The total count of CFU of filamentous fungi was greater for grains of wheat infested. The results obtained indicate that all samples of grain stored, analyzed in the initial time and 135 days, with and without infestation, for use at temperatures of 20, 25 and 30 ᵒC, are within the maximum tolerable limit of 3000 μg of deoxynivalenol per kg of wheat.